2020
DOI: 10.21608/mvmj.2020.21.2.0203
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oral ketoconazole and griseofulvin on the fertility of male rabbits

Abstract: T o inves tig ate poss ible s ide e ffe cts of ke tocona z ole a nd g ris e ofulvin on fertility of clinica lly healthy male rabbits . Design: Random iz e d controlle d experim e ntal study. Animals : Thirty mature male rabbits . Proce dure s: Ra bbits we re ra ndom ly a lloca te d into thre e e qua l siz e d g roups (10 a nimals ea ch). T he firs t g roup s e rve d as a control g roup (re ceive d no tre atm e nt), the s e cond group re ce ive d g ris e ofulvin (25 mg / kg B.W ) orally for 30 da ys , a nd the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…But, in the same study, rats with 12 weeks of stress exposure have exhibited 1.56 ± 0.12 ng/mL of testosterone which exhibits a significant elevation compared with the control. In addition to the rats, a similar study using the same dosage of ketoconazole (50 mg/kg body weight) in male rabbits also revealed a considerable drop in testosterone, measuring 0.80 ± 0.24 ng/mL, which is significantly lower when compared to the control [19]. This effect is because of the potential inhibiting effect of ketoconazole on 17, 20-desmolase, which is an enzyme that helps in the production of androgen [16].…”
Section: Discussionmentioning
confidence: 84%
“…But, in the same study, rats with 12 weeks of stress exposure have exhibited 1.56 ± 0.12 ng/mL of testosterone which exhibits a significant elevation compared with the control. In addition to the rats, a similar study using the same dosage of ketoconazole (50 mg/kg body weight) in male rabbits also revealed a considerable drop in testosterone, measuring 0.80 ± 0.24 ng/mL, which is significantly lower when compared to the control [19]. This effect is because of the potential inhibiting effect of ketoconazole on 17, 20-desmolase, which is an enzyme that helps in the production of androgen [16].…”
Section: Discussionmentioning
confidence: 84%
“…Ketoconazole is a potent inhibitor of testosterone synthesis in isolated rat Leydig cells [ 13 ] and in dispersed human, dog and rat testicular cells [ 14 ]. It has been reported that ketoconazole significantly suppressed testosterone concentrations in dogs [ 8 , 15 ], humans [ 13 , 16 ], rats [ 6 ] and rabbits [ 17 ]. Studies in rodents showed that ketoconazole also impairs spermatogenesis, leading to decreased semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…Orally administered ketoconazole was found in seminal plasma trough 30 h after dosing [ 8 ]. It has been reported that ketoconazole induced degeneration of the seminiferous tubules and arrested spermatogenesis in testes of rats [ 31 ] and rabbits [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Griseofulvin has genotoxic, carcinogenic and teratogenic effects in laboratory animals (Knasmüller et al, 1997). It has been reported to cause oligospermia in rabbits (Mohamed et al, 2020). However, von Heimendahl et al (2004) found no effect of griseofulvin treatment (25 mg/kg per day for 30 days) on semen quality in dogs.…”
Section: Antifungal Drugsmentioning
confidence: 99%